Maximum Power Point Tracking for Shaded Photovoltaic Generation Using P&O Fuzzy Logic Approach - Reddy B, Rajagopal; ., . (International Journal of Engineering and Technology, 2018)
A fuzzy logic based photovoltaic controller for shaded photovoltaic power generation is proposed based on P&O MPPT method. To obtain stable operation and maximum output, the parameters of fuzzy logic controller is adjusted in real time for various shaded conditions. The performance of proposed method of fuzzy controller is examined and validated using MATLAB/Simulink environment.